2022
DOI: 10.3389/fpls.2022.820837
|View full text |Cite
|
Sign up to set email alerts
|

The Endophytic Strain ZS-3 Enhances Salt Tolerance in Arabidopsis thaliana by Regulating Photosynthesis, Osmotic Stress, and Ion Homeostasis and Inducing Systemic Tolerance

Abstract: Soil salinity is one of the main factors limiting agricultural development worldwide and has an adverse effect on plant growth and yield. To date, plant growth-promoting rhizobacteria (PGPR) are considered to be one of the most promising eco-friendly strategies for improving saline soils. The bacterium Bacillus megaterium ZS-3 is an excellent PGPR strain that induces growth promotion as well as biotic stress resistance and tolerance to abiotic stress in a broad range of host plants. In this study, the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
5
12
0
Order By: Relevance
“…Plants in the present study also exhibited a markedly decreased Na + (root, leaf) concentration and increased K + (root, leaf) concentration after E. ludwigii B30 application under SS, which suggest that endophytic 10.3389/fpls.2022.959427 bacteria help to enhance plant development through altering ion selectivity while maintaining an increased K + content in comparison with Na + . These results agree with the study of Shi et al (2022), where endophytic strain B. megaterium ZS-3 inoculation improved the K + /Na + ratio in Arabidopsis thaliana to alleviate SS. We found increased Na + and decreased K + levels within uninoculated SS-exposed plants compared with controls, whereas there was no such effect in plants inoculated with E. ludwigii B30.…”
Section: Discussionsupporting
confidence: 92%
“…Plants in the present study also exhibited a markedly decreased Na + (root, leaf) concentration and increased K + (root, leaf) concentration after E. ludwigii B30 application under SS, which suggest that endophytic 10.3389/fpls.2022.959427 bacteria help to enhance plant development through altering ion selectivity while maintaining an increased K + content in comparison with Na + . These results agree with the study of Shi et al (2022), where endophytic strain B. megaterium ZS-3 inoculation improved the K + /Na + ratio in Arabidopsis thaliana to alleviate SS. We found increased Na + and decreased K + levels within uninoculated SS-exposed plants compared with controls, whereas there was no such effect in plants inoculated with E. ludwigii B30.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research showed that many bacteria belonging to Bacillus could help maintain ion homeostasis in plants. For instance, Bacillus subtilis prevented the decline of K + concentration in salt‐treated durum wheat and Bacillus megaterium ZS‐3 can help the plant to limit excessive Na + uptake through downregulating HKT1 in Arabidopsis thaliana (Martynenko et al, 2022; Shi et al, 2022). The FaSOS1 gene encodes a Na + /H + antiporter NHX, which plays an important role in maintaining low Na + concentration and ion dynamic balance in the cytoplasm (Keisham et al, 2018; Zhang & Shi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For analysis of ROS accumulation, the O 2 − in the B03S leaves was stained with NBT (Yuanye, Shanghai, China) according to the methods of Kumar [ 64 , 65 ]. First, the leaves were cut into 10 cm long samples and immersed in phosphate buffer (pH 7.5) consisting of 2 mM NBT, 42 mM Na 2 HPO 4 and 8 mM NaH 2 PO 4 , followed by vacuum infiltration at room temperature for 12 h. The NBT and O 2 − combined, forming visible blue stains in the leaves.…”
Section: Methodsmentioning
confidence: 99%